2022
DOI: 10.3389/fgene.2022.894865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immunological Characteristics and Immune Subtypes Based on Single-Sample Gene Set Enrichment Analysis Algorithm in Lower-Grade Glioma

Abstract: Few breakthroughs have been achieved in the treatment of lower-grade glioma (LGG) in recent decades. Apart from the conventional pathological and histological classifications, subtypes based on immunogenomics would provide reference for individualized treatment and prognosis prediction. Our study identified four immunotypes of lower-grade glioma (clusters A, B, C, and D) by bioinformatics methods in TCGA-LGG and two CGGA datasets. Cluster A was an “immune-cold” phenotype with the lowest immune infiltration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Recently, with the development of science and technology, more and more techniques have been used to predict the prognosis of patients with tumors. Recent research has revealed that computed tomography-based radiogenomic biomarkers, 15 long non-coding RNAs (lncRNAs) 16 and single-sample gene set enrichment analysis algorithm 17 have been used to predict overall survival in tumors. Nomogram, as a classic model, is a commonly used model for predicting prognosis, especially in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the development of science and technology, more and more techniques have been used to predict the prognosis of patients with tumors. Recent research has revealed that computed tomography-based radiogenomic biomarkers, 15 long non-coding RNAs (lncRNAs) 16 and single-sample gene set enrichment analysis algorithm 17 have been used to predict overall survival in tumors. Nomogram, as a classic model, is a commonly used model for predicting prognosis, especially in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…We used the single-sample gene-set enrichment analysis (ssGSEA) to quantify the tumor immune microenvironment (TIME) associated pathways in each tissue sample. The “IOBR” package [ 22 ] was used to download and analyze the gene sets of “TME-associated pathways.” In addition, xCell, EPIC, MCPcounter, and timer algorithms were used to analyze the immune infiltration levels of cells in TME. The heatmap diagram was used to compare the differences between immune cells and TME-associated pathways in different tissues.…”
Section: Methodsmentioning
confidence: 99%
“…e "IOBR" package [22] was used to download and analyze the gene sets of "TME-associated pathways." In addition, xCell, EPIC, MCPcounter, and timer algorithms were used to analyze the immune in ltration levels of cells in TME.…”
Section: Analysis Of Tumor Immunementioning
confidence: 99%
“…In the least absolute shrinkage and selection operator (LASSO) regression analysis (33), 1,000 iterations were performed to reduce the genes, and subsequently, the above genes were subjected to multivariate Cox regression analysis to obtain the coefficients. CAF risk score was derived using the same formula as in our previous study (34,35). The OC patients in each cohort were divided into high-risk and lowrisk groups, and the cutoff value for each cohort was used as the threshold.…”
Section: Enrichment Analysismentioning
confidence: 99%